2018
DOI: 10.1128/genomea.00391-18
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality Whole-Genome Sequences for 77 Shiga Toxin-Producing Escherichia coli Strains Generated with PacBio Sequencing

Abstract: Shiga toxin-producing Escherichia coli (STEC) is an enteric foodborne pathogen that can cause mild to severe illness. Here, we report the availability of high-quality whole-genome sequences for 77 STEC strains generated using the PacBio sequencing platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
(7 reference statements)
0
21
0
Order By: Relevance
“…2019) and of the American human 2013C‐4991 EHEC O80:H2 strain (Patel et al . 2018) were included in this comparison (Table ). The genome sequences of the 52 Belgian EPEC and EHEC are available via the Bioproject PRJNA606200 and the GenBank accession numbers are listed in the Table .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2019) and of the American human 2013C‐4991 EHEC O80:H2 strain (Patel et al . 2018) were included in this comparison (Table ). The genome sequences of the 52 Belgian EPEC and EHEC are available via the Bioproject PRJNA606200 and the GenBank accession numbers are listed in the Table .…”
Section: Methodsmentioning
confidence: 99%
“…To study the genetic relationships between bovine EHEC, human EHEC and bovine EPEC O80, the newly identified bovine EHEC and EPEC were genome sequenced using Illumina sequencers (Table S1) along with (i) six bovine EPEC from a previous study (Thiry et al 2017) and (ii) 10 human EHEC identified in 2018/2019 at the Belgian National Reference Centre (NRC) STEC. In addition, the previously sequenced genomes of 17 Belgian EHEC and EPEC O80:H2 (nine human EHEC isolated between 2009 and 2016, six bovine EPEC isolated between 2009 and 2015 and two bovine EHEC isolated from a single calf in 1987) (Thiry et al 2017;De Rauw et al 2019) and of the American human 2013C-4991 EHEC O80:H2 strain (Patel et al 2018) were included in this comparison (Table S1). The genome sequences of the 52 Belgian EPEC and EHEC are available via the Bioproject PRJNA606200 and the GenBank accession numbers are listed in the Table S1.…”
Section: Genome Sequencing and Gene Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Two reference E. coli O45:H2 strains (FWSEC0003 and 2011C-4251) were obtained from the NCBI database to facilitate the genomic analyses of virulence and antibiotic resistance genes of STEC O45 strains. E. coli clinical O45:H2 (FWSEC0003) was previously isolated from human feces in Canada [35], and the E. coli O45:H2 strain (2011C-4251) was isolated from samples of human feces obtained in the United States [36]. The virulence gene profiles of six strains (four experimental strains and two reference strains) were obtained using VirulenceFinder 2.0 [37].…”
Section: Determination Of Virulence and Antibiotic Resistance Genesmentioning
confidence: 99%